KONTRIBUSI KETERAMPILAN MEMBACA APRESIATIF TEKS CERITA RAKYAT TERHADAP KETERAMPILAN MEREPRODUKSI CERITA RAKYAT SISWA KELAS X SMAN 1 BATIPUH TANAH DATAR - Rizki, Muhammad; Nursaid, Nursaid; Rasyid, Yulianti (Universitas Negeri Padang, 2018)
ABSTRACT This article was at revealing the contribution the students’ reading appreciative folklore to the skills of reproducing folklore in class X SMA Negeri 1 Batipuh Tanah Datar. The data of the research were the result of the test on reading appreciative folklore and the skills of reproducing folklore. The data were gotten through an objective test intended to measure the student’s reading appreciative folklore and a performance test intended to measure the students skills of reproducing folklore. Based on the research findings and discussions, three conclusions were drawn. First, reading appreciative folklore of the students’ in class X SMA Negeri 1 Batipuh Tanah Datar was in more than adequate category (82,56). Second, the skills of reproducing folklore of students’ in class X SMA Negeri 1 Batipuh Tanah Datar was in more than adequate category (79,37). Third, there was a significant contribution between the students’ reading appreciative folklore with the skills of reproducing folklore in class X SMA Negeri 1 Batipuh Tanah Datar in which the significance level 95% with the degrees of freedom n-1 (dk = n-1). Based on hypothesis test-t was accepted because tarithmetic > ttable, is 2,14 >1,68. Kata kunci: kontribusi, keterampilan, membaca apresiatif, menulis, cerita rakyat